The occurrence of Listeria monocytogenes in mass catering: An overview in the European Union. (August 2016) - Osimani, Andrea; Clementi, Francesca
Highlights: Many foods served at the mass catering can be a source of Listeria monocytogenes . Improper cleaning and inadequate cold chain controls are common risk factors. Cross-contamination from raw materials to ready-to-eat foods is a main risk factor. The correct application of good hygiene practices can reduce the risks. Training of staff is a pivotal measure for preventing listeriosis outbreaks. Abstract: Listeria monocytogenes is the causative agent of the human illness called listeriosis. The data reported in the last 15 years of scientific literature concerning the relationship between this microorganism and the catering sector showed a permanent presence of the opportunistic pathogen through the years, though with low frequencies. Even though the pathogenic capacity of L. monocytogenes is practically circumscribed to a few risk categories as pregnant women, newborns and different kinds of immunocompromised people, given its high case-fatality rate this disease represents the second cause of death for foodborne infection in Europe. As it emerged from the reviewed literature, L. monocytogenes was recovered in many different food categories, which testifies the widespread of the pathogen in the food chain. The main causes of L. monocytogenes presence were poor microbiological quality of raw materials, cross-contamination, inadequate cleaning practices, improper storage temperature, inadequate preparation processes, and a lack in the training of staff on food hygiene. In particular, cross-contamination of foods can be reduced by hand washing, use of gloves, separation of raw materials from end products, sanitation and disinfection of equipment and food contact surfaces, hence, a structured training program of staff on these practices is essential.